Fetal Cerebral Ventricular Dilatation: Etiopathogenic Study of 130 Observations. Issue 19 (31st July 2017) - Darouich, Sihem; Boutaud, Lucile; Bessières, Bettina; Bonnière, Maryse; Martinovic, Jelena; Mechler, Charlotte; Alby, Caroline; Bernard, Jean‐Pierre; Roth, Philippe; Ville, Yves; Malan, Valerie; Vekemans, Michel; et al.
Abstract : Background: Fetal cerebral ventricular dilatation (CVD) is a common abnormal prenatal finding that often predicts a poor prognosis. The etiology involves both genetic and nongenetic factors with diverse pathogenic mechanisms. We describe the neuropathological features of CVD in a large cohort of fetuses. The goals are to determine the physiopathological mechanisms and etiologies. Methods: We retrospectively analyzed a series of 130 fetuses examined at the Necker University Hospital following termination of pregnancy between January 2000 and December 2014. Chiari II and Dandy‐Walker malformations were excluded from our study population. Karyotype and/or array comparative genomic hybridization were performed in all cases. Targeted Sanger sequencing or next generation sequencing were carried out in 34 and 5 cases, respectively. Results: We distinguished four groups of pathological entities: (1) midbrain/hindbrain patterning defects (54 cases, 42%), mainly related to aqueduct of Sylvius anomalies (atresia or stenosis); (2) cerebral cytoarchitectonic disorders (16 cases, 12%), essentially resulting from arachnoidal neuroglial ectopia; (3) hemorrhagic and perfusion failure (42 cases, 32%); and (4) nonspecific CVD (18 cases, 14%), without apparent obstruction, cortical malformation, or clastic injury. Although the pathogenic mechanisms of CVD were identified in 86% of cases, the causes, both acquired and genetic, were recognized in 21% of cases only. Conclusion: The neuropathological analysis is a powerful tool in the diagnosis of the fetal CVD pathogenic mechanisms and to identify homogeneous groups. The paucity of molecular diagnosis, notably in the major groups of midbrain/hindbrain patterning defects and hemorrhagic and perfusion failure, highlights the needs of future research to improve our current knowledge on CVD causes. Birth Defects Research 109:1586–1595, 2017. © 2017 Wiley Periodicals, Inc.